DAMPAK HUKUM AKIBAT KETERLAMBATAN PENYAMPAIAN KETERBUKAAN INFORMASI OLEH EMITEN (Studi Kasus: PLAS – PT Polaris Investama Tbk) - Gabriella Kurniawan; Richard Chandra Adam (Jurnal Hukum Adigama, 2022)
In the realm of capital markets where the issuer as a party offering its shares and the public being part of the shareholders , the public has the right to know how the issuer carries out operations ranging from information that is assembled with the issuer's business to management and financial statements on an issuer. The information provided to the public by an issuer greatly affects the selling power of the shares offered by the issuer so that it becomes a consideration for shareholders and potential investors who will invest in shares in the issuer, so that if the disclosure of issuer information as stipulated in Regulation I-E - Decree of the Board of Directors of the Indonesia Stock Exchange Number KEP-00066/BEI/09-2022 of 2022 Regarding Changes to Regulation Number I-E concerning the Obligation to Submit Information not being available to the public can be detrimental to shareholders and even bring legal consequences for the issuer itself as experienced by the Issuer PT Polaris Investama Tbk (PLAS) who trades shares on the Indonesia Stock Exchange Development Board. This research uses normative juridical research method with descriptive analytical research. The approach applied by the author is statute approach, conceptual approach, and case approach.